Effects of Lending Policies on Loan Performance of Selected Commercial Banks in Kisii County, Kenya - Abugah, Wesley Manono; Nyagol, Michael O.; Odoyo, Fredrick (IRJAES, 2017)
Lending policy is a word that used by bank employees to as a determinant of rejecting or granting loan request. Loan performance of most commercial banks in Kisii County, Kenya reveals that there is a challenge to the banking sector; the acceptance of loan reports of performance is unclear on to what extent they affect lending policies and their links to certain commercial banks. This paper analyzes the effect of lending policies on loan performance of selected commercial banks operating in Kisii County. The research used descriptive survey approach because the units of more than one and their operational features were not the same because of varying situations of the respondents. In response rate, a target population size was 270 employees and a sample size of 244 was usable in the study representing 36.4% of population size. The paper used s content validity as it measures the magnitude of validity of a content to for which the sample of the sample of the items’ representation was designed for measurement. Quantitative data was analyzed using descriptive statistics tools. The results and findings of this study, would help commercial banks in Kisii County to identify whether repayment period policy, interest rates policy or collateral policy affect the performance of loans positively or negatively, so that they can be able to minimize the risks of nonperforming loans.
Keywords: Lending policy; loan performance; interest rate policy; repayment period; collateral policy